2013
DOI: 10.1371/journal.pntd.0002420
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating Malaria from Dengue Fever in Endemic Areas: Clinical and Biological Criteria, Prognostic Score and Utility of the C-Reactive Protein: A Retrospective Matched-Pair Study in French Guiana

Abstract: BackgroundDengue and malaria are two major public health concerns in tropical settings. Although the pathogeneses of these two arthropod-borne diseases differ, their clinical and biological presentations are unspecific. During dengue epidemics, several hundred patients with fever and diffuse pain are weekly admitted at the emergency room. It is difficult to discriminate them from patients presenting malaria attacks. Furthermore, it may be impossible to provide a parasitological microscopic examination for all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 20 publications
(22 reference statements)
5
46
1
2
Order By: Relevance
“…It is therefore difficult to differentiate these 3 infections on the basis of the clinical condition alone. A previous study showed that fever may be prolonged in cases of concurrent infections [15] . Thus, laboratory diagnosis along with the clinical symptoms might assist the clinicians in making an accurate diagnosis.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is therefore difficult to differentiate these 3 infections on the basis of the clinical condition alone. A previous study showed that fever may be prolonged in cases of concurrent infections [15] . Thus, laboratory diagnosis along with the clinical symptoms might assist the clinicians in making an accurate diagnosis.…”
Section: Discussionmentioning
confidence: 94%
“…It has been previously shown that a dengue and malaria co-infection requires special attention because a delayed diagnosis and inappropriate treatment can result in fatal complications [16,17] or an aggravated host immune response [18] . In some patients, concurrent infections are more severe than mono-infections [15,18] ; others show no difference between co-infections and isolated infections [19] . Thus, an appropriate, differential, and timely diagnosis of pathogens and the correlation with disease severity of mono-versus coinfections are important for effective patient management.…”
Section: Discussionmentioning
confidence: 98%
“…4,6,14 Níveis isolados de proteína C reativa (PCR) podem ser, nos locais onde se tenha acesso ao teste, um biomarcador útil para diferenciar doentes com baixo risco de malária e dengue em áreas onde as doenças coexistam. 15 O tratamento é de suporte. 4,6 Fluidoterapia, repouso no leito e antipiréticos podem ser suficientes nas formas não graves.…”
Section: Resultsunclassified
“…It is most prevalent in tropical and subtropical regions around the world, predominantly in urban and semi-urban regions (Muhammad et al, 2015). In tropical and subtropical countries, outbreak of dengue results in thousands of deaths, human suffering and massive economic losses (Epelboin et al, 2013 a-f Means±standard deviations (SD) followed by same letter within rows indicate no significant difference (Duncan's multiple range test, P<0.05). LC50, LC90, lethal concentration at 50% and 90%; LCL, lower confidence limits; UCL, upper confidence limits.…”
Section: Discussionmentioning
confidence: 99%
“…In tropical countries like India, outbreak of dengue result in thousands of hospital admissions, human suffering and massive economic losses however, early recognition and prompt treatment can lower the risk of developing this severe disease (Epelboin et al, 2013). However, there are no available vaccines or effective antiviral agents against the virus.…”
Section: Introductionmentioning
confidence: 99%